Production of high quality packaging paper from bamboo asam pulp with cellulose nanocrystals - Moradbak, Amin (2016)
Bamboo is a non-wood fiber that has been proven to be a viable alternative source for pulp and paper industry. However, due to the large variation in species, anatomical structure and chemical composition, significant variations in the performance of paper made from bamboo have been reported. Like softwood, paper made from bamboo can have excellent properties particularly in stiffness, bending quality, tear strength, and crush resistance, which are found suitable for paperboard. Kraft pulping is the most common method used for bamboo because it generates relatively high pulp yield and kappa number with value approximately 46.4% and 24.6, respectively. Kraft paper however tends to be lower in initial brightness and has limited chemical penetration. Having strong bundle sheathes, impenetrable epidermis, a complete absence of ray cells, and limited area of conducting tissues, bamboo requires a more rigorous pulping regime as compared to wood. This study employed alkaline sulfite anthraquinone with methanol (ASAM) method of pulping for bamboo (Gigantochloa scortechinii) with a main aim to develop high performance paper for packaging application. ASAM pulping process has combined advantages of suitable paper properties obtained from kraft pulping, and higher initial pulp brightness, obtained from sulfite pulping. Low kappa number, high pulp yield, and high paper strength are the main advantages of ASAM pulping in comparison with kraft. In addition, ASAM pulping reduces the bad odor from methyl mercaptan that is generated in kraft pulping. The objectives of the study were: (I) to characterize the basic properties of Gigantochloa scortechinii bamboo fiber (II) to determine optimum pulping condition with maximum pulp yield and under less severe pulping conditions (III) to develop high strength bleached bamboo papers by applying minimum beating revolution (IV) to evalutate the effects of cellulose nanocrystals (CNC) on the properties of bamboo paper. The study was divided into: (1) evaluation of biometric characteristics and chemical composition Gigantochloa scortechinii bamboo; (2) determination of the effect of pulping conditions on the pulp and paper properties, (3) evaluation of beating and bleaching effects on the pulp and paper properties, and (4) improvement of paper properties by adding cellulose nanocrystals (CNC). Compared to cellulose fiber, CNC has many advantages such as unique optical properties, high specific strength, and high surface area. Therefore, in this study, CNC was prepared from bleached bamboo ASAM pulps and applied as an additive to improve paper properties such as the permeability, tensile, burst, and tear indices. Franklin (1954) and TAPPI standard methods were used to determine the biometric characteristics and chemical compositions of bamboo culms, respectively. The results show that bamboo has fiber length similar to that of softwood (1980 - 4000 μm), a runkel ratio of 0.86 and and flexibility ratio of 50.19. Bamboo contains 47.67% cellulose, 68.33% holocellulose, 26% lignin and 3.69% solvent extractive, which are also within the range of wood from softwoods species. The pulping was conducted using ASAM process at 170C and alkali ratio (Na2SO3/NaOH: anthraquinone: methanol) of (80/20: 0.1%: 15%). It was found that the highest yield (52.36%) was achieved by applying 14% sodium hydroxide and 90 min cooking time whilst the lowest kappa number (10.38) was observed using 18% and 120 min. Further increase of both alkali and cooking time resulted in marked decrease in both kappa number and pulp yield. The optimum pulping condition was obtained at 16% alkali and 90 min cooking time with resulting kappa number of 14.17 and pulp yield of 49.06%. The tear, tensile, and burst indices of unbleached bamboo ASAM paper were within the range of 26.33-18.64 mN.m²/g, 24.8-17.87 Nm/g, and 10.83-9.27 kPa.m²/g, respectively, which is suitable for packaging paper. The study revealed that the optimum ASAM pulping parameters was at 16% NaOH and 90 min cooking time, resulting in paper having tensile index of 20.86 Nm/g, tear index of 22.64 mN.m²/g and brightness of 39.32%. Bleaching study was conducted on bamboo pulps that have been digested using the optimized pulping conditions, 170°C, 16% NaOH and 90 min. The final brightness of bamboo ASAM pulp was 84% ISO suggesting an almost pure cellulose have been obtained. To improve the paper properties of bleached-beaten bamboo paper, cellulose nanocrystals (CNC) was added. The same ASAM bleached bamboo pulp was used to produce the CNC. For this purpose, the bleached pulp was reacted with sulfuric acid (64%) at 45C for 45 min with dynamic stirring. The CNC was analysed under UTHSCSA image Tool and the final diameter of the CNC was found to be between 10 to 20 nm.